1989
DOI: 10.1002/pola.1989.080271007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of polyurethanes containing s‐triazine rings in the main chain

Abstract: SynopsisEight new diisocyanate monomers containing s-triazine ring have been prepared from the parent diacids via the Curtius rearrangement of the corresponding diacyl azides. The parent diacids were synthesised by the reaction of pand m-hydroxybenzoic acid with 6-methoxy-2,4dichloro-s-triazine, 6-phenoxy-2,4-dichloro-s-triazine, 6-phenyl-2,4-dichloro-s-triazine, and 2-diphenylamino-4,6-dichloro-s-triazine respectively. Polyurethanes have been synthesised by solution polymerization of these diisocyanates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…For example, Sarwade et al 6 studied the synthesis of poly(cyanurate)s containing s-triazine groups in the main chain by the polyaddition of diisocyanate monomers containing s-triazine groups with ethylene glycol; Fyee et al 7 reported the synthesis of polyfunctional crosslinking agents containing both cyanate ester and epoxy groups; Abed et al 8 examined the synthesis of phosphorus monomers containing aryl cyanate ester groups; and Snow and Buckley 9 also reported the synthesis and thermal-curing reaction of cyanate esters containing fluoromethylene linkage in these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sarwade et al 6 studied the synthesis of poly(cyanurate)s containing s-triazine groups in the main chain by the polyaddition of diisocyanate monomers containing s-triazine groups with ethylene glycol; Fyee et al 7 reported the synthesis of polyfunctional crosslinking agents containing both cyanate ester and epoxy groups; Abed et al 8 examined the synthesis of phosphorus monomers containing aryl cyanate ester groups; and Snow and Buckley 9 also reported the synthesis and thermal-curing reaction of cyanate esters containing fluoromethylene linkage in these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge in polyurethane science and technology is to broaden the application window by retaining the above features, whilst enhancing characteristics such as fire performance and heat resistance 3, 4. One widely explored route to achieve this is to modify polyurethanes with thermally stable heterocyclic groups such as oxazolidone, isocyanurate, imide, triazine, phosphazene and azomethine 5–10. Blending with thermally stable polymers is another area of extensive research for improving the thermal performance of polyurethanes 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…However, low service temperature of polyurethane based electrical insulators is still a challenging problem [7]. Two main strategies were followed for the improvement of low thermal stability of polyurethanes: (1) chemical modification via introduction of heterocyclic structures [8][9][10][11][12], and (2) modification through blending with more thermally stable polymers [13][14][15][16]. Blending is a relatively simple and fast way in comparison with the chemical modification of polyurethanes backbone.…”
Section: Introductionmentioning
confidence: 99%